METHODOLOGICAL ISSUES OF INTRODUCING THE CREDIT-MODULE SYSTEM IN VOCATIONAL EDUCATION (Web of Teachers: Inderscience Research, 2024)
This article explores the methodological issues associated with introducing the credit-module system (CMS) in vocational education. The CMS is a flexible and competency-based framework designed to enhance the learning process by dividing educational programs into modular structures assessed through credits. While widely recognized for its benefits, such as flexibility, individualization, and alignment with labor market needs, the implementation of CMS in vocational education raises several challenges. This study examines the key methodological concerns, including curriculum design, assessment methods, faculty preparedness, and technological integration. By analyzing international experiences and providing practical recommendations, this article offers a roadmap for successfully integrating CMS into vocational education systems.